Mechanical ventricular assist device as a bridge to recovery post‐ABO‐incompatible heart transplantation for failed Fontan circulation. (29th March 2014) - Seitz, Stefanie; Buchholz, Holger; Rebeyka, Ivan; Ross, David; West, Lori; Urschel, Simon
Summary A girl received an ABO‐incompatible heart transplantation (ABOiHTx) at the age of 3.5 years for failed univentricular palliation with protein‐losing enteropathy (PLE). She was born with a hypoplastic left heart syndrome and underwent multistage palliation to a Fontan circulation at 2½ years of age. After the Fontan surgery, she developed PLE, necessitating a Fontan revision, followed by a Fontan takedown and eventually HTx, which was performed with a blood group B heart into an O recipient. Right ventricular (RV) failure secondary to increased pulmonary vascular resistance (PVR) evolved immediately after HTx. A temporary right ventricular assist device (RVAD) was implanted and later switched to a pneumatic pulsatile RVAD. With the adaption of PVR on the RVAD, the PLE resolved and the RVAD was explanted. In the following 12 months, she developed multiple relapses of PLE which eventually resolved after exchange of the calcineurin inhibitor.